Professional Perceptions of Six Sigma’s Value - Myrick, Jerusha; Burkhardt, Tracy; Nelms, Linda; Patch, Steve; Yearout, Robert (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> At the 2008 American Society of Quality (ASQ) World Conference on Quality and Improvement in Houston, Texas, generational diversity and knowledge transfer were two areas of focus. Quality methodology and tools have not changed much over the years. However, these practices and techniques have been repackaged and sold to upper management as the latest and greatest cure for what ails the company. With each acceptance of a repackaged methodology aging professionals are replaced by advocates of the latest methods that promise greater productivity. Lean Six Sigma and Six Sigma are the current corporate management approaches that have been marketed widely. The selling point for such initiatives is the promise that a large return on investment (ROI) can be realized. A survey was developed to compare the cost of implementing a program such as Lean Manufacturing, Six Sigma or Lean Six Sigma for various size organizations. The survey, which was divided into an initial and a follow-on survey, was administered to professionals who are employed in some field where implementations have been perceived as successful to one extent or another. The survey’s focus was to explore whether there are situations where the promise is not kept and/or where there are situations where the impact of the cultural change does not justify the effort. Based upon the occupations of the volunteer subjects, there is a very high possibility of a positive bias in the results. While survey results were generally quiet supportive of the methodologies and would lead to a recommendation for the adoption of one of the programs, it is necessary for there to be further study. <!--EndFragment-->